Efektivitas Pembelajaran Blended Learning dengan Menggunakan Google Classroom - Rahmat, Febri; Purwantono, Purwantono; Nurdin, Hendri; Putra, Randi Purnama (ALSYS, 2025)
Blended learning using Google Classroom is a combination of face-to-face and online learning that utilizes the Google Classroom platform to facilitate interactions between students and teachers outside the classroom. This study aims to assess the effectiveness of implementing blended learning using Google Classroom. The study employs a quantitative method with a descriptive research design. It involves 27 students from the Grade XI Industrial Mechanical Engineering program at SMK Negeri 1 Sumatera Barat. Data collection was conducted through questionnaires and documentation The questionnaire in this study assessed five aspects: the use of Google Classroom, interaction in learning, technological accessibility, comfort and satisfaction, and the effectiveness of blended learning. The analysis results for each assessed aspect were as follows: the use of Google Classroom at 76.66%, interaction in learning at 71.29%, technological accessibility at 75.37%, comfort and satisfaction at 70.74%, and the effectiveness of blended learning at 68.51%. This indicates that students’ overall response to the effectiveness of blended learning using Google Classroom was 73.19%, categorized as effective.